A video-based situational judgement test of medical students' communication competence in patient encounters: Development and first evaluation. Issue 5 (May 2022) - Reiser, Sabine; Schacht, Laura; Thomm, Eva; Figalist, Christina; Janssen, Laura; Schick, Kristina; Dörfler, Eva; Berberat, Pascal O.; Gartmeier, Martin; Bauer, Johannes
Highlights: SJTs are efficient measures of medical students' communication competence. We developed and evaluated a construct-driven, video-based online-SJT. Data from experts and medical students underscore curricular and content validity. Acceptance and usability were estimated positive by experts and students. Test reliability was high, irrespective of the used scoring method. Abstract: Objective: We developed and evaluated the Video-Based Assessment of Medical Communication Competence (VA-MeCo), a construct-driven situational judgement test measuring medical students' communication competence in patient encounters. Methods: In the construction phase, we conducted two expert studies ( n panel1 = 6, n panel2 = 13) to ensure curricular and content validity and sufficient expert agreement on the answer key. In the evaluation phase, we conducted a cognitive pre-test ( n = 12) and a pilot study ( n = 117) with medical students to evaluate test usability and acceptance, item statistics and test reliability depending on the applied scoring method (raw consensus vs. pairwise comparison scoring). Results: The results of the expert interviews indicated good curricular and content validity. Expert agreement on the answer key was high ( ICCs > .86). The pilot study showed favourable usability and acceptance by students. Irrespective of the scoring method, reliability for the complete test (Cronbach's α >.93) and its subscales (α >.83) was high. Conclusion: There is promising evidence that medical communication competence can be validly and reliably measured using a construct-driven and video-based situational judgement test. Practice Implications: Video-based SJTs allow efficient online assessment of medical communication competence and are well accepted by students and educators.